COMPARATIVE ASSESSMENT OF TAP WATER, BOTTLED WATER, AND POINT-OF-USE TREATED WATER: A SYNTHETIC LITERATURE REVIEW BASED ON STUDIES FROM IRAN AND PAKISTAN (World Bulletin of Public Health, 2026)
Access to safe drinking water remains a central determinant of public health, socioeconomic stability, and sustainable development. Urban populations across developing and middle-income countries increasingly rely on multiple water sources—municipal tap water, bottled water, and point-of-use (PoU) treated water—to meet their daily needs. This article presents a combined literature review and analytical synthesis of two comparative studies conducted in Bandar-e-Abbas, Iran, and Abbottabad, Pakistan. Both investigations examine physicochemical and microbiological water quality parameters while also exploring consumer perceptions, economic implications, and public health consequences. By integrating findings from these geographically and socioeconomically distinct contexts, this review highlights similarities and divergences in water quality outcomes, consumer trust, regulatory performance, and infrastructure reliability. The analysis demonstrates that while physicochemical compliance with international standards is frequently achieved, microbiological safety and public confidence remain variable. Ultimately, the review underscores the importance of strengthening municipal infrastructure, enhancing public communication, and developing evidence-based policy strategies to ensure equitable access to safe drinking water.